THE FUNDAMENTAL CONTRADICTION OF THE GOALS AND MEASURES OF THE "AFFIRMATIVE ACTION" POLICY IN THE USA - Pokrovsky, Anatoly; Lementova, Yevheniia (Collection of scientific papers «ΛΌГOΣ», 2023)
A demonstration of discrimination and a fight against it is shown in different societies. The more developed a society is, the more complicated its structure is, and the more varied the population is. Development is always accompanied by differential processes that require secondary integration at a new level of complexity. Under such circumstances, the desire of developed societies to positively solve integration problems, including in the field of ethno-cultural relations, which are an important form of social interaction in any society, is obvious. The problem of ethno-cultural integration becomes even more acute if there is a certain historical context in which these relations were formed. A clear example of such a problematic situation is the modern USA, where the great racial and ethno-cultural diversity of the population is complemented by the historical legacy of slave ownership and a long policy of segregation of certain sections of the population. The consequence of these circumstances was a significant deformation of social relations, to overcome which the state policy of "affirmative actions" has been implemented over the past few decades. In modern conditions, gender issues have also been added to the ethnic component. Analysis of the goals and means of this program seems important and relevant in modern conditions.